2018
DOI: 10.1016/j.redox.2018.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen peroxide derived from NADPH oxidase 4- and 2 contributes to the endothelium-dependent vasodilatation of intrarenal arteries

Abstract: The role of NADPH oxidase (Nox)-derived reactive oxygen species in kidney vascular function has extensively been investigated in the harmful context of oxidative stress in diabetes and obesity-associated kidney disease. Since hydrogen peroxide (H2O2) has recently been involved in the non-nitric oxide (NO) non-prostanoid relaxations of intrarenal arteries, the present study was sought to investigate whether NADPH oxidases may be functional sources of vasodilator H2O2 in the kidney and to assess their role in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 55 publications
4
39
1
Order By: Relevance
“…Moreover, liraglutide upregulated NOX4 (NADPH oxidase 4), which has been demonstrated to provide beneficial effects on vasodilator function in mice and rat renal arterioles by production of hydrogen peroxide [34, 35]. Surprisingly, the expression of NOS3 which synthesizes nitric oxide (NO) was downregulated by liraglutide in the NTN model.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, liraglutide upregulated NOX4 (NADPH oxidase 4), which has been demonstrated to provide beneficial effects on vasodilator function in mice and rat renal arterioles by production of hydrogen peroxide [34, 35]. Surprisingly, the expression of NOS3 which synthesizes nitric oxide (NO) was downregulated by liraglutide in the NTN model.…”
Section: Discussionmentioning
confidence: 99%
“…Within the vasculature, ROS contribute to basal endothelial cell proliferation/migration [ 39 , 40 ], as well as smooth muscle cell differentiation [ 41 ]. ROS can also participate in vasomotor responses such as autoregulation [ 42 ], endothelium-dependent vasodilation [ 43 , 44 ], flow-mediated vasodilation [ 45 ], hypoxic pulmonary vasoconstriction (HPV) [ 46 , 47 ] and hyperoxia-induced vasoconstriction [ 48 , 49 , 50 ]. At physiological concentrations, H 2 O 2 elicits vasodilation in the pulmonary circulation [ 51 , 52 , 53 , 54 ] and diminishes HPV in CH animals [ 55 ].…”
Section: Ros In the Pathogenesis Of Phmentioning
confidence: 99%
“…The novel inhibitors ML171 and GKT136901 selectively inhibit NOX1 and NOX1/NOX4, respectively. [46][47][48][49][50] Clinical trials with 170 patients have demonstrated that the novel inhibitors are well-tolerated and non-toxic, and thus provide a good alternative for DPI. [50] In this study, we controlled for the possible unspecific effects of DPI by additionally analysing intracellular ROS levels after inhibition of NOX1 and NOX1/4 by the selective inhibitors.…”
Section: Discussionmentioning
confidence: 99%